Pembaruan Hukum Islam tentang Empat Saksi Laki-Laki Non-Muslim dalam Kasus Li'an - Mansyur, Zaenudin (Fakultas Syariah IAIN Purwokerto, 2019)
Changes in the field of law are important matters that cannot be prevented by anyone, including Islamic law related to civil and criminal law. Specifically, in the discussion of Islamic criminal law regarding allegations of adultery (li'an), the accuser who is obliged to bring four male Muslim witnesses can turn into four non-Muslim male witnesses, because it is based on strong arguments so that non-Muslims who were initially illegitimate as witnesses become allowed. The change in law became apparent when an argument that said anyone could be a witness provided that the terms and conditions were sufficient as a witness. The legality of the four non-Muslim male witnesses is very strong when there is an argument based on the word of God regarding four witnesses who are not clearly stated whether they are Muslims or non-Muslims. Likewise, the reason that today's society is a modern and pluralistic society can provide a view of freedom for non-Muslim communities to stand witnesses to defendants in li'an cases or accusations of adultery.